Zmartwychwstanie Chrystusa − zmartwychwstanie nasze - Rubinkiewicz, Ryszard (The Biblical Annals, 2017)
The author shows what Christ’s resurrection consist in and how the resurrection of all the dead has been placed in the Resurrection of the Saviour. To this effect he analyzes the texts from 1 Cor and from the Book of Revelation, and he considers the type and way of the resurrection of all the people. He comes to a conclusion that resurrection is not a physical or biological phenomenon but an event about which one may speak only in an analogical way. It is a shift to a totally different way of existence, which for the righteous consists in permanent sojourn with Christ.